IMPLEMENTASI MAQASHID SYARI’AH DALAM MENGHADAPI WABAH COVID-19 - Nirmalasanti Anindya Pramesi; Nazarudin Nazarudin (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2020)
The Covid-19 virus outbreak which had become a global pandemic has led to new policies to prevent the spread and transmission of the virus. One of them was the policy of worship for Muslims which MUI and Hai'ah Kibar Ulama Al-Azhar responded to. The method used in this research was descriptive qualitative which was carried out by describing an object strictly, regularly, carefully, and objectively. This study aimed to determine the implementation of Maqashid Syari'ah from the existence of law issued by the scholars in the face of the current emergency. Maqashid syari'ah was kind of goals to be achieved from a legal stipulation. The law of the failure of the obligation to perform Friday prayers and congregational prayers arised because of the risk of harm to oneself and others, so this can became the age of sharia (sad al dzariah) so that it was permissible to leave it. There were real conditions that were at risk of triggering harm in the midst of an epidemic, then this could be used as' illat or something of a substantial nature that affects the existence of a law.